2018
DOI: 10.2136/vzj2018.07.0132
|View full text |Cite
|
Sign up to set email alerts
|

Assessing SMAP Soil Moisture Scaling and Retrieval in the Carman (Canada) Study Site

Abstract: Core Ideas• Upscaling methods compared in situ measures with soil moisture from the SMAP satellite. • The accuracy of SMAP soil moisture products in annual cropland was assessed. • The spatial representativeness of sparse in situ networks was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 42 publications
(57 reference statements)
4
32
0
Order By: Relevance
“…10 These domains were established to coincide with the SMAP Core Validation Sites operated by the USDA Agricultural Research Service near Ames, Iowa (42.03 N, 93.62 W; South Fork), and Agriculture and Agri-food Canada (AAFC) near Winnipeg, Manitoba (49.90 N, 97.14 W). 11 The South Fork experimental watershed covers an area of ∼1300 km 2 and has a subhumid climate with an average annual precipitation of 800 mm. 12 The crop land portion is dominated by two row crops, corn, and soybeans.…”
Section: Study Sitesmentioning
confidence: 99%
“…10 These domains were established to coincide with the SMAP Core Validation Sites operated by the USDA Agricultural Research Service near Ames, Iowa (42.03 N, 93.62 W; South Fork), and Agriculture and Agri-food Canada (AAFC) near Winnipeg, Manitoba (49.90 N, 97.14 W). 11 The South Fork experimental watershed covers an area of ∼1300 km 2 and has a subhumid climate with an average annual precipitation of 800 mm. 12 The crop land portion is dominated by two row crops, corn, and soybeans.…”
Section: Study Sitesmentioning
confidence: 99%
“…The arithmetic average (Method 1) was calculated for unflagged data from each in situ location within the given EASE2 pixel (Table 2) at 36, 9, and 3 km at each depth and the SD calculated for each hour. This approach was evaluated by others and found to be robust, particularly when replication was sufficient within the spatial extent (Adams et al, 2015; Clewley et al, 2017; Bhuiyan et al, 2018).…”
Section: Network Implementationmentioning
confidence: 99%
“…4a) affect the distributions by increasing the maximum allowed sampling distances because the surface soil moisture becomes more homogeneously distributed in space due to the typically quite widespread precipitation in that region. The opposite occurs during dry periods because evaporation, draining, and runoff over various soil and land cover types tend to create spatially heterogeneous soil moisture distributions, which typically reaches its maximum at intermediate soil moisture levels (Brocca et al, 2010).…”
Section: Soil Moisturementioning
confidence: 99%
“…Qin et al (2013) suggested the use of MODIS-derived apparent thermal inertia to interpolate between in situ soil moisture measurements. So far, the required sampling density is discussed only concerning in situ measurements, which heavily depend on sensor quality and network location (Vereecken et al, 2008;Brocca et al, 2010;Bhuiyan et al, 2018). Higher station numbers are necessary, as well as the establishment of general rules for their selection .…”
Section: Introductionmentioning
confidence: 99%